In Situ Characterization of the Lithosphere‐Asthenosphere System beneath NW Pacific Ocean Via Broadband Dispersion Survey With Two OBS Arrays - Akiko Takeo; Hitoshi Kawakatsu; Takehi Isse; Kiwamu Nishida; Hajime Shiobara; Hiroko Sugioka; Aki Ito; Hisashi Utada (Geochemistry, Geophysics, Geosystems)
Abstract We conducted broadband dispersion survey by deploying two arrays of broadband ocean bottom seismometers in the northwestern Pacific Ocean at seafloor ages of 130 and 140 Ma. By combining ambient noise and teleseismic surface wave analyses, dispersion curves of Rayleigh waves were obtained at a period range of 5–100 s and then used to invert for one‐dimensional isotropic and azimuthally anisotropic βV (VSV) profiles beneath each array. The obtained profiles show ~2% difference in isotropic βV in the low‐velocity zone (LVZ) at a depth range of 80–150 km in spite of the small difference in seafloor ages and the horizontal distance of ~1,000 km. Forward dispersion‐curve calculation for thermal models indicates that simple cooling models cannot explain the observed difference and an additional mechanism, such as sublithospheric small‐scale convection, is required. In addition, the fastest azimuths of azimuthal anisotropy in the LVZ significantly deviate from the current plate motion direction. We infer that these observations are consistent with the presence of small‐scale convection beneath the study area. As for azimuthal anisotropy in the Lid, the peak‐to‐peak intensity is 3–4% at the depth from Moho to ~40 km. The fastest direction is almost perpendicular to magnetic lineation in area A at 130 Ma and oblique to magnetic lineations in area B at 140 Ma, suggesting complex mantle flow beneath the infant Pacific Plate surrounded by three ridge axes. The intensity of azimuthal anisotropy in the LVZ is ~2%, indicating that radial anisotropy is stronger than azimuthal anisotropy therein.